Transcriptional mechanisms underlying thiazolidine-4-carboxylic acid (T4C)-primed salt tolerance in Arabidopsis - Hsu, Wei-Yung; Wu, Yi-Zhen; Lin, Yu-Min; Zheng, Mei-Juan; Chen, Liang-Jwu; Yeh, Chuan-Ming (Plant cell reports, 2025)
Key Message T4C enhances salt stress tolerance in Arabidopsis by regulating osmotic and oxidative stress responses, activating ABA-related pathways, and inducing stress-responsive genes, including LEA proteins . High soil salinity is a major environmental stress that restricts crop productivity worldwide, necessitating strategies to enhance plant salt tolerance. Thiazolidine-4-carboxylic acid (T4C) has been reported to regulate proline biosynthesis, which is essential for abiotic stress responses, yet its role in stress tolerance remains unclear. This study investigates the physiological and molecular effects of T4C on Arabidopsis thaliana under salt stress conditions. T4C treatment alleviated salt-induced growth inhibition, improving biomass, relative water content, and chlorophyll retention while reducing oxidative stress markers such as malondialdehyde and anthocyanin accumulation. Transcriptomic and quantitative PCR analyses revealed that T4C upregulated proline biosynthesis genes, ABA-dependent signaling ( RD29b , ABI3 ), and Late Embryogenesis Abundant ( LEA ) genes. Gene Ontology (GO) enrichment analysis identified biological processes related to water deprivation, ABA signaling, and salt stress, while Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated the involvement of phenylpropanoid biosynthesis, plant hormone signal transduction, and MAPK signaling in T4C-mediated responses. Notably, several transcription factors, including NAC, MYB, and WRKY family members, were identified as candidates involved in T4C-mediated stress priming. Collectively, these findings suggest that T4C may enhance salt tolerance by modulating osmotic balance, reducing oxidative stress, and activating stress-responsive genes and transcriptional regulators. Our results provide novel insights into the molecular mechanisms underlying T4C-mediated stress responses, highlighting its potential as a chemical priming agent to improve plant resilience under saline conditions.